Melatonin attenuates cisplatin-induced acute kidney injury in rats via induction of anti-aging protein, Klotho. (July 2019) - Ko, Je-Won; Shin, Na-Rae; Jung, Tae-Yang; Shin, In-Sik; Moon, Changjong; Kim, Sung-Ho; Lee, In-Chul; Kim, Sung-Hwan; Yun, Won-Kee; Kim, Hyoung-Chin; Kim, Jong-Choon
Abstract: This study investigated the protective effects of melatonin (MT) against cisplatin (CP)-induced acute kidney injury in rats as well as its possible mechanism of action associated with anti-aging protein Klotho. The following four experimental groups were evaluated: vehicle control, CP (7 mg/kg), CP&MT20 (20 mg/kg/day), and CP&MT40 (40 mg/kg/day). The concomitant administration of MT significantly ameliorated CP-induced acute kidney injury in rats, as evidenced by increased kidney weight, increased serum levels of blood urea nitrogen and creatinine, and increased incidence of histopathological alterations with renal tubular cell apoptosis. In addition, MT treatment protected kidney tissue against oxidative damages and significantly upregulated the expression level of Klotho decreased by CP treatment, resulting in reduced phosphorylation of protein kinase B (AKT) and forkhead box O (FOXO) as well as reduced expression levels of B-cell lymphoma 2-associated X protein (Bax) and caspase-3. MT not only partially regulated oxidative stress via AKT/FOXO signaling, but also reduced apoptosis caused by CP by inhibiting the Bax/caspase-3 pathway. Our results indicated that MT could prevent acute kidney injury induced by CP in rats, presumably through upregulating the expression of Klotho, resulting in elevated anti-oxidant and anti-apoptotic properties. Highlights: Melatonin (MT) attenuated acute kidney injury induced by cisplatin (CP). MT upregulated the expression level of Klotho decreased by CP treatment. Upregulated Klotho attenuated oxidative stress and apoptosis induced by CP.